Business Feasibility and Strategic Development of the Majas Craft Bouquet Enterprise in Pekalongan, Indonesia - Khofifatul Alivia; Muhammad Taufiq Abadi (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study examines the business feasibility and strategic development of Majas Craft, a microenterprise engaged in handmade bouquet production in Pekalongan, Central Java, Indonesia. Using a qualitative descriptive approach, the research explores key dimensions of business feasibility, including human resources, management, production, marketing, and financial performance. Data were obtained through in-depth interviews, field observation, and documentation involving the owner, employees, and customers. The findings reveal that Majas Craft demonstrates strong business potential supported by increasing market demand, product uniqueness, and customer satisfaction. The enterprise’s competitive advantages lie in product creativity, affordable pricing, and direct customer engagement through social media. However, challenges remain in digital marketing adoption, production scalability, and managerial formalization. Financial analysis indicates a positive profit margin and short capital turnover, confirming the enterprise’s operational feasibility. The study concludes that sustainable growth requires strengthening digital marketing strategies, enhancing production efficiency, and improving entrepreneurial capacity through continuous learning. This research contributes to the growing literature on microenterprise feasibility and creative economy development in Indonesia’s local business context.